Characterizing the spatial distributions of soil biota at a legacy base metal mine using environmental DNA. (January 2022) - Kavehei, Armin; Gore, Damian B.; Chariton, Anthony A.; Hose, Grant C.
Abstract: Characterizing the distribution of biota in response to contaminants is a critical element of site risk assessments. In this study we investigated the spatial distributions of biota and soil chemistry data in surface soil from Sunny Corner, a legacy base metal sulfide mine, Australia. Our results showed that copper (Cu), zinc (Zn), arsenic (As) and lead (Pb) in the surface soil exceeded Australian national soil quality guidelines and posed risks to the environment. Environmental (e)DNA metabarcoding of prokaryote and eukaryote composition confirmed the suggestion of environmental risk posed by these elements collectively explaining 72.9 % and 60.5 % of the total variation in the composition of soil prokaryotes and eukaryotes, respectively. Prokaryotic taxa from the phyla Gemmatimonadetes, Verrucomicrobia and Deinococcus-Thermus showed similar spatial patterns to As and Pb, and were positively correlated. Eukaryotic taxa from the phylum Chlorophyta had similar positive correlations with As and Pb in the soil. In contrast, Amoebozoa and Cercozoa, were sensitive to metals and metalloids, having higher relative abundances in soils with lower concentrations of contaminants. Our study shows that metabarcoding is a promising ecological approach for rapid, large scale assessment of contaminated and potentially impacted sites. Graphical abstract: Image 1 Highlights: Spatial patterns of soil biota reflect contamination at a legacy base metal mine. Gemmatimonadetes and Deinococcus-Thermus abundance correlated with soil As and Pb. Amoebozoa and Cercozoa were negatively correlated with metals and metalloids. eDNA metabarcoding is effective for large scale assessment of contaminated sites.